The Adverse Effect of Spasticity on 3-Month Poststroke Outcome Using a Population-Based Model - S. R. Belagaje; C. Lindsell; C. J. Moomaw; K. Alwell; M. L. Flaherty; D. Woo; K. Dunning; P. Khatri; O. Adeoye; D. Kleindorfer; J. Broderick; B. Kissela (Stroke Research and Treatment)
Several devices and medications have been used to address poststroke spasticity. Yet, spasticity’s impact on outcomes remains controversial. Using data from a cohort of 460 ischemic stroke patients, we previously published a validated multivariable regression model for predicting 3-month modified Rankin Score (mRS) as an indicator of functional outcome. Here, we tested whether including spasticity improved model fit and estimated the effect spasticity had on the outcome. Spasticity was defined by a positive response to the question “Did you have spasticity following your stroke?” on direct interview at 3 months from stroke onset. Patients who had expired by 90 days (n=30) or did not have spasticity data available (n=102) were excluded. Spasticity affected the 3-month functional status (β=0.420, 95 CI=0.194 to 0.645) after accounting for age, diabetes, leukoaraiosis, and retrospective NIHSS. Using spasticity as a covariable, the model’s R2 changed from 0.599 to 0.622. In our model, the presence of spasticity in the cohort was associated with a worsened 3-month mRS by an average of 0.4 after adjusting for known covariables. This significant adverse effect on functional outcomes adds predictive value beyond previously established factors.